Qualitative endline results of the tipping point project to prevent child, early and forced marriage in Nepal - Cari Jo Clark; Kayla Jashinsky; Emma Renz; Irina Bergenfeld; Robert L. Durr; Yuk Fai Cheong; Sadhvi Kalra; Anne Laterra; Kathryn M. Yount (Taylor & Francis Group, 2023)
ABSTRACTCurrently, Nepal is not on track to meet Sustainable Development Goal 5.3 - the elimination of harmful practices, including child, early and forced marriage by the year 2030. Evidence on what works to prevent child, early and forced marriage often is inattentive to contextual factors that influence intervention effectiveness. This study presents qualitative results of a mixed-methods evaluation of CARE's Tipping Point Program to prevent child, early and forced marriage in Nepal, interrogating the perceived benefits of the programme and elucidating contextual features that enhance or detract from programme benefit. Baseline data included interviews with adolescent girls (N = 20), boys (N = 10), adult community leaders (N = 8) and focus group discussions (FGDs) with girls (N = 8 groups; 48 individuals), boys (N = 8 groups; 47 individuals) and parents (N = 16 groups; 95 individuals). Using thematic analysis and structured comparisons by time, gender, district, caste/community, stakeholder type and arm, we found diverse programme participation, but widespread improvements in knowledge across several domains, with behavioural changes concentrated among participants with stronger participation and pre-programme characteristics suggestive of low risk of child marriage. Findings underscore the need to address structural barriers to prevent child marriage and the challenges of attributing programme benefit amidst a dynamic social context.